Colaboração entre corporações e startups: um estudo de caso da Liga Emerging Technologies - Pizzolato, Vinicius (Universidade do Vale do Rio dos Sinos, 2021)
Corporations and startups develop different capabilities in their paths and processes of innovation. Corporations have resources, experience and client base, but they are bond to their history and run into their lack of agility, internal bureaucracy and aversion to risk-taking. Startups are agile and bold, without bureaucratic structures, but they do not have resources as abundantly as the corporations. Among the collaboration strategies between corporations and startups, the corporate accelerators have been calling the attention of academic researchers. Collaborative innovation initiatives demand networking capabilities, which are the set of organizational routines and activities implemented by the enterprises that empanel an interorganizational network to initiate, maintain, develop and terminate relationships on behalf of the network. Such capabilities impact directly the interactions between the participants and the paths the knowledge travels in the innovation network, as well as the efficacy and the management of collaborative innovation programs between corporations and startups. This dissertation aims to propose a framework for the collaboration between corporations and startups based on the networking capabilities. It is associated to the line of action of Innovation and Sustainability of the Professional Program in Business Management (PPGN). Grounded on collaborative innovation, corporate acceleration programs designing and networking capabilities concepts, analysis frameworks were elaborated, which gave support to the studies about how these themes manifest in a corporate acceleration program. A single-case study was conducted, which analyzed the Liga Emerging Technologies acceleration program coordinated by the accelerator Liga Ventures, and counted with the participation of four corporations and nine startups. The data triangulation has been done through documentary analysis, direct observation and the conducting of twelve interviews with the startups CEOs and with the accelerator’s and corporations’ employees. Through the thematic analysis, six different themes have been studied: antecedents to the networking capabilities, network initiating capability, network maintaining capability, network developing capability, network terminating capability and outcomes from the corporate acceleration program. The research showed that the organizations must dispose of antecedents such as the correct definition of the challenges to be solved and the provision of resources compatible with them. Possible outcomes of the collaborative innovation initiative were also identified, such as the development of the open innovation culture in the organization and the learning that will feed future collaborative innovation programs. From this research, a framework for collaboration between corporations and startups was proposed based on the networking capabilities, which has the practical applicability of assisting organizations that intend to develop or sponsor collaborative innovation programs through the use of a corporate accelerator. The outcomes of this dissertation can be used by them in order to better format the programs, selecting more assertive partners, developing the networking capabilities of their partners with more efficacy and better conducting the collaboration initiatives for complementary collaborative innovation strategies.
Keywords: Capacidades de rede; Aceleradoras corporativas; Inovação colaborativa; Networking capabilities; Corporate accelerators; Collaborative innovation; ACCNPQ::Ciências Sociais Aplicadas::Administração